Odd Pareto-G Family: Properties, Regression, Simulations and Applications (Contemporary Mathematics, 2023)
Several new families have been introduced in the last two decades to extend well-known distributions, and at the same time provide great flexibility for modelling real data. We propose the Odd Pareto-G family with two extra shape parameters, and obtain some of its mathematical properties, which give important information about its structure and may be useful in future research. We construct a new regression model based on a special distribution of the new family. Maximum likelihood estimation and simulations are addressed, and these results show that the estimates are consistent for different percentages of censorship. Four applications to real data show the usefulness of the new models, reveal that they are suitable for the presented data, and can be considered interesting alternatives to model censored and uncensored lifetime data.
Keywords: maximum likelihood, Odd Pareto-G family, simulation, T-X family